ABOUND.2L+: A randomized phase 2 study of nanoparticle albumin‐bound paclitaxel with or without CC‐486 as second‐line treatment for advanced nonsquamous non‐small cell lung cancer (NSCLC) - Morgensztern, D; Cobo, M; Ponce Aix, S; Postmus, PE; Lewanski, CR; Bennouna, J; Fischer, JR; Juan-Vidal, O; Stewart, DJ; Fasola, G; Ardizzoni, A; Bhore, R; et al. (Wiley, 2018)
Background This randomized phase 2 trial compared the efficacy and safety of second‐line nanoparticle albumin‐bound paclitaxel (nab‐paclitaxel) with or without the addition of CC‐486 (an oral formulation of 5‐azacytidine) in patients with advanced‐stage, nonsquamous non‐small cell lung cancer.